Ending over-lending: Assessing systemic risk with debt to cash flow - Peter Sarlin; Bruce A. Ramsay (Bank of Finland, 2014)
This paper operationalizes early theoretical contributions of Hyman Minsky and applies these in the context of economic sectors and nations. Following the view of boom-bust asset cycles, depicted by the endogenous build-up of risks and their abrupt unraveling, Minsky highlighted the relationship between debt obligations and cash flows. While leverage is oftentimes linked to the vulnerability of a nation, and hence systemic risk, one less explored measure of leverage is the debt-to-cash flow ratio (Debt/CF). Cash flows certainly have a well-known, academically verified connection to the ability of corporations to service and repay corporate debt. This paper investigates whether the relationship between the flow of a nation's savings to its stock of total debt provides a means for understanding systemic risks. For a panel of 33 nations, we explore historic Debt/CF trends, as well as apply the same procedure to individual economic sectors. This assessment of systemic risk is arranged for presentation within a four-zone framework. In terms of an early-warning indicator, we show that the Debt/CF ratio e effectively stratifies systemic risks, and offers a useful platform toward macro-financial sustainability.
URN:NBN:fi:bof-20140807258
Keywords: E21; F34; G01; H63; 330; debt-to-cash flow; debt-to-gross saving; systemic risk; four-zone framework